To Infinity and beyond …: Heterarchical Governance, the Teach for All Network in Europe and the Making of Profits and Minds - Olmedo, Antonio; Bailey, Patrick L. J.; Ball, Stephen J. (European educational research journal EERJ, 2013)
This article explores the increasing commercialisation of education through the empirical case of Teach For All, a network of social enterprises which is spreading a new model of teacher training across Europe and around the world. This model, which is supported and funded by a heterogeneous mix of public institutions and private sector organisations, is not only opening up public education to private involvement and influence, but it is also reshaping what it means to be a teacher. The substantive argument that we present here is that commercialisation is not only about making money (which is certainly being achieved through this kind of heterarchical network), but also about making people up as commercial and enterprising subjects. Drawing on the idea of neoliberalism as both a material process of economisation, and a form of governmentality, we weave together an analysis which considers the interrelations between profit, the subjectivities of the Teach For All teacher, and the governance of teacher education in Europe.